Sobre el sermó per a la festa de sant Galdric, atribuït al bisbe Oliba, i els altres textos transmesos pel fragment de còdex XIII-6 de l'Arxiu Episcopal de Vic de mitjan segle XI - Alturo i Perucho, Jesús (Miscel·lània litúrgica catalana, 2014)
Palaeographic, codicological and textual study of the fragment of the codex Ms. XIII-6, preserved in the Arxiu Episcopal de Vic, with an identification of the several texts that it transmits (St. Jerome-Isidore?s Paralipomena prologue, Augustinus? De ciuitate Dei, St. Odo of Cluny?s Vita sancti Geraldi, sermon on St. Narcissus of Girona); discussion on Oliba?s supposed authorship of the sermon writted because of the feast day of St. Galdric, which is nothing more than a cento, with a new edition; determination of the different amanuenses, all of them from the eleventh century and very closed to the circle of Benedict, canon of Vic, and new data on cultural relations between Cluny and Catalonia through Cuixà.